Hypoxic resistance training and health benefits in older adults - Concha Vilca, Carlos (2022)
During aging, genetic and environmental factors carry an increased risk of diseases that facilitate the loss of function. High-intensity resistance training has been shown to lead to health benefits in older adults, however, its use is limited in this population. Recently, hypoxic resistance training (HRT) has been presented as a viable alternative in rehabilitation therapy for older adults, however, information is scarce in this regard. Thus, the objective of this study was to collect current knowledge about HRT in older adults, as well as the benefits for their health. To do this, a selective search was carried out for articles published in the last 6 years on the effects of HRT in older people in the Pubmed database. The search resulted in 227 articles, of which 18 were selected for this review. Three types of training were identified: blood flow restriction therapy (BFRT), resistance training in hypobaric hypoxia (RTHH), and resistance training in normobaric hypoxia (RTNH). From the information collected, we can indicate that TRFS offers greater positive effects on strength gain and muscle hypertrophy, while there is little evidence of RTHH and RTNH in older people. Finally, we express the need for more studies to evaluate the safety of this intervention in health in this age group.